Mechanical and Fiber-Bridging Behavior of Slag-Based Composite with High Tensile Ductility - Jeong-Il Choi; Hyeong-Ki Kim; Bang Yeon Lee (Applied Sciences, 2020)
This paper presents an experimental and analytical investigation of the fundamental mechanism of the highly ductile behavior of strain-hardening slag-based composite reinforced by polyethylene fibers. Composite properties, including compressive strength and tensile behavior of the composite, were identified. Micromechanical characteristics, including matrix fracture toughness and interfacial properties between matrix and fiber, were investigated and the fiber-bridging behavior of the composite was simulated. The tensile behavior of the composite was evaluated by micromechanical analysis. Test results showed that the composite had extremely high tensile ductility of up to 7.5% and high tensile strength of 8.5 MPa, along with a moderate compressive strength of 36.8 MPa. Saturated cracking patterns with controlled crack width of 59.8 μm were also observed in the composite. Considering the variation of matrix properties and fiber distribution, the theoretical fiber-bridging curve simulated the tensile behavior of the composite well, and the micromechanical analysis results supported the tensile behavior of the composite.